LitU classes - Abd Rashid, Mohd Shahril; Abdullah, Anwar Fikri; Mohd Shuib, Ahmad Sofiyuddin (Universiti Teknologi MARA, Perak, 2022)
LitU Classes (LitU.C) is a web that use asynchronous learning method. To put it simple, it’s a self-learning training since it doesn’t need live participants. Students can use it with a low connection bandwidth at any time and anywhere. While books provided can be download for offline learning (cache system).